Artificial pancreas: a game changer in the diabetic management - Marupuru, Sumanth; Dudem, Veeraj; Soni, Zeal; Doshi, Dhruvi; Vummenthala, Srikar Reddy; Gummalla, Vaishnavi (International Journal of Advances in Medicine, 2024)
Diabetes mellitus (DM) is one of the world’s leading metabolic disorders, where extensive research on therapeutic management is going on. Artificial pancreas is an emerging novel therapeutic solution for diabetes mellitus based on the automatic insulin delivery system (AID). Medtronic’s MiniMed 670G System (hybrid closed loop) was the first artificial pancreas approved by food and drug administration (FAD) and currently in clinical use. Efficiency, success rate, cost, and very less usage were few major barriers for an artificial pancreas. We described the basic structure, functions, limitations, and future of the artificial pancreas.